Students’ Views On The Use Of Book And Web-Based Materials For Their Elt Classes: A Study On Ict-Based Education In Indonesian Context - Isnawati, Ida (KnE Social Sciences, 2017)
This study examined students’ views on the use of web-based materials in ELT classes. It was triggered by the findings of some previous studies done in the developed countries showing that, in this digital era, teachers and students still have not abandoned traditional materials despite the growing interest in digital/web-based materials (Allen, 2015; Jarvis and Szymczyk, 2010). Therefore, this study tried to reveal students’ attitude on their lecturers’ use of technology for ELT in Indonesian context where, as one of developing countries, the technology is booming nowadays. The focuses of this study were the students’ preference on the use of book-based and web-based materials, the motivational impacts of the use of book-based and web-based materials for the students, and the problems in using book-based and web-based materials. This study involved students of English Department at IAIN Tulungagung. They were given questionnaires on their lecturers’ materials used in their ELT classes and some of them were then interviewed in details for their further responses. The findings of this study reported the students’ real preference, advantages, and problems related to ELT materials which can be used as a reference for the lecturers or teachers in selecting the materials for their students in similar context. Key words: Book-based materials, web-based materials, technology, students’ preferences.